2018
DOI: 10.1021/acs.est.7b05575
|View full text |Cite
|
Sign up to set email alerts
|

Unified Theory of Vapor–Wall Mass Transport in Teflon-Walled Environmental Chambers

Abstract: Secondary organic aerosol (SOA) formation is studied in laboratory chambers, in which volatile organic compounds (VOCs) are oxidized to produce low-volatility compounds that condense into the aerosol phase. It has been established that such oxidized low-volatility compounds can partition into the chamber walls, which traditionally consist of Teflon film. Several studies exist in which the rates of uptake of individual vapor compounds to the chamber walls have been measured, but a unified theory capable of desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
1
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(109 citation statements)
references
References 50 publications
4
103
1
1
Order By: Relevance
“…A number of studies have demonstrated that absorptive partitioning of volatile organic compounds (VOCs) into the Teflon walls of environmental chambers can affect the results of the experiments conducted within. This partitioning has been shown to be reversible and relatively fast, on a timescale 30 of minutes (Matsunaga and Ziemann, 2010;Yeh and Ziemann, 2015;Krechmer et al, 2016;Ye et al, 2016;Huang et al, 2018). Furthermore, a recent study showed analogous absorptive partitioning of VOCs when transported through PFA (perfluoroalkoxy alkanes) Teflon tubing, with similar interaction parameters as for FEP (fluorinated ethylene propylene) Teflon chamber walls (Pagonis et al, 2017).…”
Section: Introductionmentioning
confidence: 92%
“…A number of studies have demonstrated that absorptive partitioning of volatile organic compounds (VOCs) into the Teflon walls of environmental chambers can affect the results of the experiments conducted within. This partitioning has been shown to be reversible and relatively fast, on a timescale 30 of minutes (Matsunaga and Ziemann, 2010;Yeh and Ziemann, 2015;Krechmer et al, 2016;Ye et al, 2016;Huang et al, 2018). Furthermore, a recent study showed analogous absorptive partitioning of VOCs when transported through PFA (perfluoroalkoxy alkanes) Teflon tubing, with similar interaction parameters as for FEP (fluorinated ethylene propylene) Teflon chamber walls (Pagonis et al, 2017).…”
Section: Introductionmentioning
confidence: 92%
“…RH-induced oligomer suppression has been reported for toluene and α-pinene SOA formation (Hinks et al, 2018;Huang et al, 2018a). The oligomer decrease under high RH could also be due to RH-volatility dependent organic vapor wall loss (Huang et al, 2018b). A clear m/z dependence of signal reduction under humid conditions as compared to the dry conditions is shown in Fig.…”
Section: Two-dimensional Thermogrammentioning
confidence: 92%
“…ACSM data were analyzed in Igor Pro V6.37 (Wavemetrics, Inc.) using ACSM local v1603 (Aerodyne) and other custom routines. Aerosol concentrations were corrected for depositional particle wall loss (Pathak et al, 2007) but not for organic vapor loss (Huang et al, 2018b;Krechmer et al, 2017;Nah et al, 2017).…”
Section: Environmental Chamber Experiments and Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…One impediment to the measurement of lower-volatility gases is the influence of inlet tubing and other experimental apparatus surfaces. Several recent experiments have probed the effects of Teflon chamber walls on experimental processes (Matsunaga and Ziemann, 2010;Krechmer et al, 2016bKrechmer et al, , 2017Huang et al, 2018). A variety of organic and inorganic gases have been shown to reversibly absorb into Teflon (and other polymer) tubing or reversibly adsorb onto the surface of a variety of solid materials including stainless steel (Pagonis et al, 2017;Deming et al, 2019;.…”
Section: Introductionmentioning
confidence: 99%